Disorder Type and Severity as Predictors of Mental Health in Siblings of Children with Chronic Disorders. - Fredriksen, Trude; Orm, Stian; Prentice, Caitlin M.; Kirchhofer, Solveig; Zahl, Erica; Botta, Matteo; Vatne, Torun M.; Fjermestad, Krister W. (Journal of Autism & Developmental Disorders, 2026)
Siblings of children with chronic disorders are at risk of developing mental health problems. Studies are inconclusive about whether sibling mental health is best predicted by the specific diagnoses of the child with disorder or by transdiagnostic factors. The aims of the present study were (1) to examine if specific diagnoses predicted sibling mental health, and (2) to examine if disorder severity in the child with the chronic disorder predicted sibling mental health. Baseline data from a randomized controlled trial were used. Siblings (aged 8 – 16 years) of children with chronic disorders and their parents were recruited from eight municipality and hospital clinics (N = 288). The children with chronic disorders were placed in ICD-10 diagnostic categories based on combined parent report and clinical records. Regression analyses with the most frequent primary diagnoses (ADHD, Asperger syndrome, autism, down syndrome, rare disorders) and a measure of disorder severity as predictors of sibling mental health were run. Father-reported disorder severity predicted sibling-reported internalizing problems and father-reported internalizing and externalizing problems in siblings. Mother-reported disorder severity predicted mother-reported sibling internalizing problems. No single primary diagnosis predicted sibling internalizing or externalizing problems. Disorder severity does to an extent predict sibling mental health, whereas single diagnostic categories do not. Disorder severity may be used to identify siblings at risk and/or in need of interventions. Fathers should be included in assessment and health care for siblings as their reports seem to predict sibling mental health better than the mothers.